Floodplain mapping of an ungauged river: A case study on Seti River in Pokhara, Nepal - Basnet, Keshav; Acharya, Deepak; Bhandari, Krishna Prasad; Lamichhane, Suraj; Sadadev, Biwas Babu (Himalayan Journal of Applied Science and Engineering, 2024)
Settlements and infrastructures along the banks of Seti River in Pokhara, Nepal are at high risk of flood. Floodplain mapping for ungauged Seti River is not straightforward like the one for gauged rivers. Main goal of this study was to prepare floodplain maps along the ungauged Seti River in Pokhara, as a case study, using one-dimensional HEC-RAS model. First, catchment area ratio (CAR) method was applied to find annual flow in ungauged Seti River based on flow data of gauged Mardi station. Once the annual maximum flow was estimated for sufficient time length (i.e., 42 years), peak flood was predicted using Gumbel method for various reaches of Seti River within Pokhara. Thus, estimated peak floods were also compared with the peak floods predicted using Gumbel method based on the annual flow data of Tanahu station. As the specific discharge observed to be comparable with each other (difference ≤ 2.68%), CAR method found be a reliable one that is useful for ungauged river. Then, Cowan’s approach was applied to estimate Manning’s roughness coefficient (n) and used it for calibration of HEC-RAS model. Cowan approach found to be a best alternative for ungauged river as the comparison of modelled flow depth with measured flow depth yielded only 3.82% difference. Finally, 1D hydraulic modelling was performed using calibrated HEC-RAS model with available 12.5 m resolution DEM terrain data. Floodplain maps were prepared based on the HEC-RAS simulation results coupled with Google Earth map. The flood inundation area within Pokhara was found to be 2.76, 3.05, and 3.59 Km2 for the peak flood of 20, 50, and 100 years return periods, respectively. Moreover, Laltin Bazar and Gaighat areas were identified to be at high risk of flood such that these areas found to be inundated with 20 or greater years return period floods, compared to Ramghat area which was observed to be flooded with the peak flood of 50 or more years return period. Floodplain maps of this study could be used for preparing flood hazard maps, planning infrastructures, and flood management.